2016
DOI: 10.15177/seefor.16-10
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Bosnian Pine (Pinus hedreichii Christ.) at Tree-Line Locations from Kosovo and its Response to Climate

Abstract: Background and purpose: Pinus heldreichii Christ. is a sub-endemic species occurring at tree-line locations in Kosovo and covering an area of 2500 ha. In high elevation sites radial growth is mainly controlled by low temperatures. The main purpose of this study was the analysis of radial growth of P. heldreichii and its response to local climate conditions. Materials and Methods: Research sites comprise of three high elevation stands of P. heldreichii with specific site conditions. Core samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…In our study, TRW chronologies of both species had only a weak to non-existent climate signal. This seems to be typical of both studied tree species since this characteristic has been reported by several authors [10,16,17,19]. Seim et al [17,18] reported a weak signal in P. heldreichii from Albania, despite the fact that they collected a large number of samples from three sites.…”
Section: Climate Signal In Tree-ring Widthssupporting
confidence: 77%
See 3 more Smart Citations
“…In our study, TRW chronologies of both species had only a weak to non-existent climate signal. This seems to be typical of both studied tree species since this characteristic has been reported by several authors [10,16,17,19]. Seim et al [17,18] reported a weak signal in P. heldreichii from Albania, despite the fact that they collected a large number of samples from three sites.…”
Section: Climate Signal In Tree-ring Widthssupporting
confidence: 77%
“…Teleconnection in P. heldreichii is relatively good. When comparing the P. heldreichii TRW chronology from the Murina site with other P. heldreichii TRW chronologies from other sites across the Western Balkan region we got relatively high statistical values-t BP ranges between 5.89 and 15.50 (see Table 3), which is comparable with chronologies from other researchers [16,17].…”
Section: Long Trw Chronologies and Their Potential For Dating Wooden supporting
confidence: 74%
See 2 more Smart Citations
“…In Bulgaria, maximum latewood density of P. heldreichii trees from a high-elevation stand in the Pirin Mountains is used for reconstruction of summer temperatures for the period 1768-2008 [3]. Other studies conducted in Bulgaria [5,6], Greece [7], Kosovo [8] and Albania [9], have addressed the dynamism of climate-growth relationship of this high elevation species at various scales. In Albania, a 1391-year tree-ring width (TRW) chronology (617-2008) was developed and maximum density measurements were acquired on living and dead P. heldreichii trees [9].…”
mentioning
confidence: 99%